Sino-Tibetan linguistics : critical concepts in linguistics, volume I to IV - LaPolla, Randy J. (Routledge, 2021)
The Sino-Tibetan languages form the largest language family in the world in terms of native speakers, of whom there are some 1.4 billion spread across East Asia, Southeast Asia and parts of South Asia. The family consists of two branches: Sinitic, consisting of the Chinese languages (including Cantonese and Hakka), and Tibeto-Burman, which as well as Tibetan and Burmese includes several hundred further languages spoken from the Tibetan plateau in the north to the Malay peninsula in the south, and from northern Pakistan in the west to northeastern Vietnam in the east.